Cyprus under British colonial rule : culture, politics, and the movement toward union with Greece, 1878-1954 - Ioannides, Christos P., 1946- (Lexington Books, 2019)
This study examines British rule in Cyprus from 1878 to 1954. The author analyzes the cultural and religious dimensions of Cypriot responses to British rule and the ways in which Greek Orthodox culture was a primary conduit for resistance to the colonial system.